2006
DOI: 10.1093/geront/46.1.134
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Telephone Support Groups Among Ethnically Diverse Caregivers of Persons With Dementia

Abstract: The findings demonstrate that telecommunications technology can overcome the often formidable logistical problems faced by both English- and Spanish-speaking caregivers, and it can provide benefits similar to those obtained in face-to-face support groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 21 publications
1
67
0
2
Order By: Relevance
“…any group session were assigned to group 0. Controls were also assigned to dummy groups based on date of study entry (groups [10][11][12][13][14][15][16][17][18][19]. Group (0-19) was then entered as a random effect to control for potential variability between groups that may affect outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…any group session were assigned to group 0. Controls were also assigned to dummy groups based on date of study entry (groups [10][11][12][13][14][15][16][17][18][19]. Group (0-19) was then entered as a random effect to control for potential variability between groups that may affect outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…18 That work also established the value, feasibility, and usability of telephone supports in both English-and Spanish-speaking caregivers. 19 Nevertheless, the effectiveness of telesupport has not been evaluated using randomized controlled designs.…”
Section: This Is the Author's Final Version Prior To Publication In Tmentioning
confidence: 99%
“…The value of non-pharmacological treatments [22][23][24] and social interventions [25][26][27][28] are described along with an increased general understanding amongst healthcare professions as to the multidisciplinary needs of patients and their caregivers. It has been shown that early disease stages are associated with higher patient quality of life [29] .…”
Section: Introductionmentioning
confidence: 99%
“…This type of brief support has been moderately effective for caregivers in rural areas where access to care centers is lacking (Bank, Argüelles, Rubert, Eisdorfer, & Czaja, 2006). A particular role for occupational therapy could be providing problemsolving advice and monitoring progress.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%